ALEVIS UNDER LAW: THE POLITICS OF RELIGIOUS FREEDOM IN TURKEY - Hurd, Elizabeth Shakman (Journal of law and religion, 2014)
Proponents of minority rights are calling for urgent measures to protect the Copts in Egypt, the Ahmadiyya in Pakistan, and the Baha'i in Iran to secure religious diversity, shield minority populations from discriminatory practices, and prevent the outbreak of religious violence. State governments, international organizations, nongovernmental organizations, and international tribunals promote religious liberalization as the antidote to the violence and discord that is often attributed to these divisions. Enshrined in international agreements and promoted by a small army of experts and authorities, legal protections for religious minorities are heralded as the solution to the challenges of living with social and religious diversity. This article examines how the complexities and ambivalences of ordinary religious belonging are translated and transformed through the process of becoming legalized and governmentalized. It documents the risks of adopting religion as a category to draw together individuals and communities as corporate bodies that are depicted as in need of legal protection to achieve their freedom. The argument is developed through an extended case study of the legal status of the Alevis in Turkey, a community and a category formally constituted as a single whole as part of the Turkish nation-building project. It evaluates two legal constructions of Alevism by the Turkish state and the European Court of Human Rights. While premised on differing assumptions about Alevism, both erase the indeterminacy and open-endedness surrounding Alevism as a lived tradition embedded in a broader field of social and cultural practices, while bolstering the role of the state in defining and overseeing Turkish religiosities.